Epiphytic bryophytes on Thuja orientalis in Nagaland, North-eastern India - Bansal, Pooja; Nath, Virendra; Chaturvedi, S. K. (Bangladesh Journal of Plant Taxonomy, 2011)
A survey of bryophyte diversity in district Mokokchung (Nagaland) has brought to light an unexpectedly rich bryophyte flora, including several interesting species to Nagaland. The tree species Thuja orientalis Linn. growing in Nagaland, luxuriantly covered by epiphytic bryophytes with wide range of diversity. The samplings were made from tree base up to canopy as well as abaxial and adaxial side of the tree. Investigation has revealed twelve species of mosses represented to eight families belonging to the genus Brachymenium Schwaegr., Plagiothecium B.S.G., Entodontopsis Broth., Entodon C. Muell., Erythrodontium Hamp., Fabronia Raddi, Regmatodon Brid., Floribundaria Fleisch. and Hyophila Brid., four species of hepatics belonging to two families and two genera Frullania Raddi and Lejeunea Libert compose the corticolous bryophyte vegetation of Thuja orientalis in some of the localities of Nagaland, North-east region of India. The richness and diversity of bryophytes on Thuja tree bark have been assessed for the first time. Keywords: Epiphytic bryophytes; Thuja orientalis; Nagaland; India. DOI: http://dx.doi.org/10.3329/bjpt.v18i2.9303 Bangladesh J. Plant Taxon. 18(2): 163-167, 2011 (December)